(untitled) (Innovative Technologica: Methodical Research Journal, 2022)
William Faulkner is one of the America’s greatest modernist writers who won the 1949 Nobel Prize for Literature was awarded in 1950. This article is devoted to analyze the usage of symbolism and symbols in the famous novel by a prominent writer William Faulkner “Absalom, Absalom!”. “Absalom, Absalom!” is a novel which depicts the details of the Thomas Sutpen’s story that was told by different characters, relationship with the people around him such as his sons, wife, Miss Rose and society where he was surrounded. The objective of the article is to describe some symbols used in the novel. The use of symbolism occurs a great deal throughout the novel. Symbolism has a very deep and perceptive understanding of the novel “Absalom, Absalom!”. There are a wide range of various usual symbolic subjects, such as Miss Rose herself, her sister Ellen and Sutpen’s children. By analyzing these symbolic subjects, we can get a better comprehension of this novel. Each of the symbols helps the author to create a good story.